2020
DOI: 10.1242/dev.176750
|View full text |Cite|
|
Sign up to set email alerts
|

Neurogenesis in the inner ear: the zebrafish statoacoustic ganglion provides new neurons from a Neurod/Nestin-positive progenitor pool well into adulthood

Abstract: The vertebrate inner ear employs sensory hair cells and neurons to mediate hearing and balance. In mammals, damaged hair cells and neurons are not regenerated. In contrast, hair cells in the inner ear of zebrafish are produced throughout life and regenerate after trauma. However, it is unknown whether new sensory neurons are also formed in the adult zebrafish statoacoustic ganglion (SAG), the sensory ganglion connecting the inner ear to the brain. Using transgenic lines and marker analysis, we identify distinc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 72 publications
(85 reference statements)
0
5
0
Order By: Relevance
“…To evaluate the impact of magnetite during embryonic neurogenesis, as mentioned before, we treated embryos with magnetite (MT) (100, 200, and 400 µg/mL) and then fixed them at 96 hpf. To evaluate the effects of magnetite on neural progenitor cells, we analyzed the expression levels of the nestin gene, described as the main marker of these precursors [ 35 ]. Embryos treated with magnetite showed a significant dose-dependent reduction in nestin -expressing cells in the ventricular forebrain (FV) and the post-midbrain (PM) compared to non-treated embryos ( Figure 7 a).…”
Section: Resultsmentioning
confidence: 99%
“…To evaluate the impact of magnetite during embryonic neurogenesis, as mentioned before, we treated embryos with magnetite (MT) (100, 200, and 400 µg/mL) and then fixed them at 96 hpf. To evaluate the effects of magnetite on neural progenitor cells, we analyzed the expression levels of the nestin gene, described as the main marker of these precursors [ 35 ]. Embryos treated with magnetite showed a significant dose-dependent reduction in nestin -expressing cells in the ventricular forebrain (FV) and the post-midbrain (PM) compared to non-treated embryos ( Figure 7 a).…”
Section: Resultsmentioning
confidence: 99%
“…For the analysis of the transcript levels, we used, as a control, genes that are known to be related to hearing or HL and whose expression pattern in the mouse IE was similar to that observed for the genes Cnrip1 , Ppp3r1 , and Plek [ 33 ]. Thus, eight genes were selected: Eya4 (DFNA10) [ 38 ] and Dfna5 ( Gsdmea and Gsdmeb ) [ 39 ] due to high evidence of association with HL ( ; accessed on 1 July 2021); Pou4f1 and Elavl4 due to high expression in sensory neurons on the statoacoustic ganglion of zebrafish, equivalent to the spiral ganglion in mice [ 31 , 40 ]; Scl1a3a because its expression is mostly in the IE of zebrafish and with a possible role in hearing in mice [ 40 , 41 , 42 , 43 ]; and Gab1 , known to be an essential structure in the tyrosine kinase/HGF receptor pathway of the MET/MET/HGF proto-oncogene and responsible for the HL associated with DFNB26 and its modifier Mettl1 [ 44 ]. The choice of these two genes had, as a parameter, the fact that the CNRIP1 and PPP3R1 genes are related to cancer in humans.…”
Section: Methodsmentioning
confidence: 99%
“…The inner ear becomes less accessible as bone hardens and tissues become opaque with age. But research indicates that the vestibular system continues to develop and change as the fish grows in adulthood ( Ehrlich and Schoppik, 2019 ; Schwarzer et al, 2020 ). Investigation of adult vestibular hair cells, afferents, and circuits, in addition to the current neurobiological research in larval and juvenile fish, will complete our understanding of mature vestibular function.…”
Section: Summary and Future Directionsmentioning
confidence: 99%
“…Zebrafish are known to regenerate hair cells continuously throughout their lifespan, but do not necessarily regenerate afferent neurons. Studies have demonstrated that new neurons are developed in the SAG from 48 hpf well into late juvenile stages (28 dpf) ( Schwarzer et al, 2020 ). However, new neurons are few in the adult, indicating that new hair cells regenerated in mature fish are likely innervated by preexisting neurons ( Schwarzer et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation